2022
DOI: 10.1002/ldr.4165
|View full text |Cite
|
Sign up to set email alerts
|

Microbial inoculation to improve plant performance in mine‐waste substrates: A test using pigeon pea (Cajanus cajan)

Abstract: Mining activities alter soil physicochemical and biological properties that are critical for plant establishment. Revitalisation of soil biological properties via microbial inoculations can potentially be adopted to improve vegetation restoration. Here, we evaluate the feasibility of using beneficial microorganisms in the form of commercially available inoculants to enhance plant performance in a non‐toxic and infertile mine‐waste substrate, using pigeon pea [Cajanus cajan (L) Millsp.] as a test plant. Six tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 90 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…Interestingly however, neither of the microbial amendments ameliorated this, indicating that they did not provide the requisite bacteria to restore normal nodule development. Previous work with commercial microbial products, testing a rhizobia product and a mixed bacteria-and-fungi product on pigeon pea has shown that in some situations they can successfully increase the number of root-nodules, although in this work the inoculums did not improve measured plant-growth parameters relative to control treatments [ 74 ], while another study on pigeon pea identified three non-rhizobial isolates that promote nodule number and fresh weigh as well as plant growth, but only when co-inoculated with the rhizobial bioinoculant strain IC3123 [ 75 ]. It is also worth considering that evidence from previous studies indicates that the incorporation of targeted microbes into extruded pellets might be challenging, with microbe viability potentially declining due to osmotic stress [ 76 ] or desiccation [ 77 ] during the drying of the freshly-formed pellets.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly however, neither of the microbial amendments ameliorated this, indicating that they did not provide the requisite bacteria to restore normal nodule development. Previous work with commercial microbial products, testing a rhizobia product and a mixed bacteria-and-fungi product on pigeon pea has shown that in some situations they can successfully increase the number of root-nodules, although in this work the inoculums did not improve measured plant-growth parameters relative to control treatments [ 74 ], while another study on pigeon pea identified three non-rhizobial isolates that promote nodule number and fresh weigh as well as plant growth, but only when co-inoculated with the rhizobial bioinoculant strain IC3123 [ 75 ]. It is also worth considering that evidence from previous studies indicates that the incorporation of targeted microbes into extruded pellets might be challenging, with microbe viability potentially declining due to osmotic stress [ 76 ] or desiccation [ 77 ] during the drying of the freshly-formed pellets.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies have indicated that inoculated PSB can markedly improve soil properties (Mahdi et al, 2020; Tahir et al, 2018). To a great extent, microorganisms in inoculants may influence plant development and nutrient uptake (Spohn et al, 2020; Tandon et al, 2022; Wong et al, 2022). In this study, we found that inoculated XQP35 and SQP80 treatments significantly increased maize biomass and the relative chlorophyll content (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…available synthetic consortia, and locally sourced microbial inoculum (LSM). While the functional capacity can be preserved by applying inoculum (Kumaresan et al, 2017), such inoculum has had mixed success in establishing microbial communities and affecting plant growth for potential usefulness in ecosystem restoration, including mine soils and tailings (Frewert et al, 2022;Li et al, 2023;Middleton & Bever, 2012;Moreira-Grez et al, 2019;Trippe et al, 2021;Wong et al, 2022;Wubs et al, 2016). While lime would be the primary agent to increase soil pH, and BS or F can serve as sources of plant nutrients, biochar (BC) has a limited potential to raise pH and supply nutrients (Chintala et al, 2014;Hou et al, 2022).…”
Section: Core Ideasmentioning
confidence: 99%
“…To accelerate the formation of soil microbial communities, several studies have examined the use of microbial inoculum in the form of soil transplants, commercially available synthetic consortia, and locally sourced microbial inoculum (LSM). While the functional capacity can be preserved by applying inoculum (Kumaresan et al., 2017), such inoculum has had mixed success in establishing microbial communities and affecting plant growth for potential usefulness in ecosystem restoration, including mine soils and tailings (Frewert et al., 2022; Li et al., 2023; Middleton & Bever, 2012; Moreira‐Grez et al., 2019; Trippe et al., 2021; Wong et al., 2022; Wubs et al., 2016).…”
Section: Introductionmentioning
confidence: 99%